Exploration of the motivations in the adherence of patients to periodontal maintenance therapy. - Héctor Oñate; Macarena Cuadro; Francisca Hasell; Francisco Fuentes (Universidad de Concepción., 2022)
Introduction: Although it has been shown that the supportive periodontal therapy (SPT) is essential to maintain the results obtained by periodontal therapy, patient adherence to SPT is not usually satisfactory (4). The objective of this research is to explore the motivations in the adherence to periodontal maintenance of patients treated at Universidad Viña del Mar (UVM) during the year 2020. Material and Methods: A study based on the qualitative paradigm was carried out using a design based on discourse analysis through semi-structured interviews. A sample size of 10 participants was consolidated, by obtaining with them the saturation of data collected and of 4 main dimensions. Each interview was transcribed ad verbatim and later analyzed through the Atlas.ti 9 Software. Results: Four main categories or dimensions were created: Motivations of the patients to produce a change in their oral health; Information that the patients have regarding their oral health; Oral hygiene habits acquired after periodontal treatment; Situations that prevent adherence to periodontal treatment. Conclusion: The main motivations of patients to adhere to supportive periodontal therapy are related to the education and information they acquire in the first phase of periodontal treatment. Observing the changes during treatment, improving oral health, improving aesthetics and functionality, are other important motivations, as well as the patients' fear of losing their teeth and the desire to educate their family.